Cleaner Fish Labroides dimidiatus Presence Does Not Indirectly Affect Demersal Zooplankton - Grutter, Alexandra S.; Nishikawa, Natsumi; Uribe-Palomino, Julian; Richardson, Anthony J. (Frontiers in Marine Science, 2022)
Coral reef mutualisms involve complex trophic ecological relationships that produce indirect effects. Excluding mutualistic cleaner fish Labroides dimidiatus from reefs indirectly increases the abundance of many fishes and reduces demersal stages of their ectoparasitic prey (gnathiid isopods). Whether cleaners affect populations of planktivorous fishes that consume demersal zooplankton, and consequently indirectly affect the rest of the demersal zooplankton community — via presumed changes in planktivory — is unknown. Therefore, using a long-term cleaner fish manipulation on patch reefs (July 2000 to December 2012, Great Barrier Reef), we tested whether cleaner treatment (removal or control) affects planktivorous fish abundance and diversity, and demersal zooplankton biomass, abundance, and diversity. Fish surveys, 9 and 12 years after removing cleaners revealed fewer fish on removal compared to control reefs for one of the three most abundant planktivores, but not total abundance (Pomacentridae, 26 species), diversity, and composition. Emerging zooplankton were sampled during the day and night over nine sampling trips across 12 years. There was no effect of cleaner treatment on post-removal values, compared with pre-removal values in July 2000, for zooplankton biomass, abundance, diversity, and composition (34 taxa). Zooplankton abundance showed no diel differences, but diversity, and occasionally biomass, were higher at night. Zooplankton composition also showed diel differences, with three taxa contributing the most to this dissimilarity [Cirripeda nauplii, Facetotecta (Arthopoda), Oikopleuridae (Chordata)]. Zooplankton diversity did not differ among times, abundance was higher in January 2002 relative to July 2000, and composition differed among all times. The lack of detectable indirect effects of cleaner fish presence on zooplankton (non-gnathiid) may partly be due to cleaners’ variable effect on planktivorous fish abundance, but also the result of invertebrate planktivory and other processes that affect zooplankton populations not investigated here. Nevertheless, the pronounced diel and temporal changes in zooplankton observed likely influence coral reef trophic interactions.